Analisis Hak Waris Anak dalam Perkawinan Beda Agama: Tinjauan Komprehensif Berdasarkan Burgerlijk Wetboek - Ni’matul Fauziyah S. A. P; Krisnajaya Farhan Saputra; Syalaizha Febtria Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage in Indonesia is regulated by Law Number 1 of 1974 which requires implementation according to religious law, but interfaith marriages often cause problems, especially in inheritance rights. Indonesia recognizes three inheritance law systems: Islamic, civil, and customary, which regulate inheritance differently. Children from interfaith marriages often face inheritance obstacles, especially if there are differences of faith between the testator and the heirs. Several court decisions provide inheritance rights through a mandatory will, but are limited to one-third of the inheritance. Existing solutions include preparing a clear will, mediating disputes, and involving a notary to validate documents. A comprehensive approach through legal education and collaboration between the government, non-governmental organizations, and the community is needed to provide legal certainty and justice for children from interfaith marriages.